Indirect Vs. direct systems of business finance: theory and evidence - Bhole, L.M. (1998)
The question of a choice between the primacy of the credit-based financial system and that of the capital-based system has been widely debated abroad. However, there has been a great lack of awareness of the importance of this issue in India. While traditionally, the Indian financial system has been primarily credit-based, efforts have been made in recent years to make it far more capital market-based than it has been in the past. This paper argues for the preservation of the primacy of the banks and other financial institutions because of their very many special advantages and services. - Reproduced
Keywords: Business finance; Banks